Evaluation of the splenic injury following exposure of mice to bisphenol S: A mass spectrometry-based lipidomics and imaging analysis - Chao Zhao (Environment International, 2020)
Background: The widespread use of bisphenol A (BPA) substitutes has aroused great attention towards their toxicological evaluation in vivo and in vitro. Considering the intimate correlation between BPA and metabolic diseases, we explored whether bisphenol S (BPS), a major substitute to BPA, could cause the splenic toxicity by disturbing the lipid metabolism in mouse model. Methods: We investigated the splenic injury by combing the mass spectrometry (MS)-based lipidomics and imaging analysis, as well as molecular biological methods. Mice were divided into three groups (control-olive oil, 10 and 100 μg-BPS/kg body weight/day group) and treated by BPS in 56 days. Results: Two of BPS-treated concentrations induced the splenic morphological alterations and inflammation, including the decreased numbers and cellularity in the periarteriolar lymphoid sheath (T cell zone) and paucicellular primary lymphoid follicles (B cell zone) in splenic white pulp. Lipidome profiling of spleen after BPS treatment was also changed with up-regulated sphingosine [So], neutral glycosphingolipids [CerG], cholesteryl ester [ChE], diacylglycerols [DAG], lysophosphatidylcholine [LPC], lysophosphatidylethanolamine [LPE], phosphatidylglycerols [PG], phosphatidylinositols [PI] and phosphatidylserine [PS] as well as down-regulated ceramide [Cer], phosphatidylethanolamines [PE] and sphingomyelin [SM] compared to the control group. More importantly, significant different lipids in abundance and spatial distribution also implicated that white pulp were more sensitive to BPS treatment than other splenic sub-structures. Signaling lipids such as So (d18:0), Cer (d18:1/24:0), Cer (d18:1/22:0), SM (d18:1/22:1) and SM (d18:1/24:2) associated with inflammation were remarkable changed and co-localized in the splenic white pulp. Conclusions: Our finding indicated that BPS exposure promoted the splenomegaly, pro-inflammatory activation and morphological alterations, as well as induced the lipidome perturbation in the immune cells of white pulp, which might be expected to contribute a new perspective of bisphenol-induced organ injury. Keywords: Bisphenol S, Splenic injury, Mass spectrometry imaging, Lipidomics, Splenic white pulp